The centrality of shame experiences: Psychometric properties of the Portuguese version of the Centrality of Event Scale - Matos, Marcela (2010)
The nature of shame experiences suggests they can function as traumatic and autobiographical memories, central to a person’s identity and life story, with an impact on the vulnerability to psychopathology. The current study explores the psychometric properties of the portuguese version of the Centrality of Event Scale (CES; Berntsen & Rubin, 2006) in a normal population sample of 811 subjects. Principal Components Analysis was conducted to examine construct validity. Results support the one dimensional structure underlying CES, explaining 59% of the variance. We found item-total correlations ranging from moderate to high (> .65) and a high internal consistency (α=.96), indicating an excellent reliability of the scale. Convergent and divergent validity was confirmed by the high correlations found with IES-R and by the moderate correlations with DASS Depression, Anxiety and Stress (...) DOI: http://dx.doi.org/10.17575/rpsicol.v24i1.297